2012
DOI: 10.3389/fpsyg.2012.00202
|View full text |Cite
|
Sign up to set email alerts
|

Orienting of Attention to Gaze Direction Cues in Rhesus Macaques: Species-Specificity, and Effects of Cue Motion and Reward Predictiveness

Abstract: Primates live in complex social groups and rely on social cues to direct their attention. For example, primates react faster to an unpredictable stimulus after seeing a conspecific looking in the direction of that stimulus. In the current study we tested the specificity of facial cues (gaze direction) for orienting attention and their interaction with other cues that are known to guide attention. In particular, we tested whether macaque monkeys only respond to gaze cues from conspecifics or if the effect gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, since monkey faces are covered with fur, the smoothed (blurred) skin texture may appear to be less realistic. It has been shown that monkeys prefer viewing real conspecific faces rather than unrealistic cartoon faces (Yu et al, 2012 ). Therefore, different perceptions of blurring facial texture between monkeys and humans may account for the different findings between these two species.…”
Section: Discussionmentioning
confidence: 99%
“…However, since monkey faces are covered with fur, the smoothed (blurred) skin texture may appear to be less realistic. It has been shown that monkeys prefer viewing real conspecific faces rather than unrealistic cartoon faces (Yu et al, 2012 ). Therefore, different perceptions of blurring facial texture between monkeys and humans may account for the different findings between these two species.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 1 showed that for an apparatus with six containers and a 30 s delay, the monkeys made a great number of errors and they used spatial information to solve the task. Previous experiments on attention in humans and rhesus macaques (Ciaramitaro et al, 2001; Yu et al, 2012); navigation in capuchin monkeys (Presotto & Izar, 2010) and facial recognition in chimpanzees (Rosenfield et al, 2019); in which spatial information plays a role, have shown that adding discriminative stimuli, such as color, can improve the accuracy of the subjects in each task. Studies with rhesus macaques in nonnavigational tasks, have shown that adding colors to spatial positions reduces the disruption in memory caused by the administration of kynurenate in the hippocampus (Forcelli et al, 2014).…”
Section: Experiments 2: Could Spider Monkeys Improve Their Memory?mentioning
confidence: 99%